Characterization and reconstruction for stochastically distributed void morphology in nano‑silver sintered joints. (November 2020) - Qian, Cheng; Sun, Zhongchao; Fan, Jiajie; Ren, Yi; Sun, Bo; Feng, Qiang; Yang, Dezhen; Wang, Zili
Abstract: Driven by sintering kinetics, stochastically distributed voids exist inevitably in nano‑silver sintered joints to affect their electrical, mechanical and thermal properties, reliability, etc. In this paper, a holistic approach including both void morphology characterization and reconstruction stages is developed for the reconstruction of Stochastically Distributed Void Morphologies (SDVMs) in nano‑silver sintered joints. A set of dispersion parameters, including area A, distance l, angle α, and aspect ratio δ, are firstly proposed for quantitatively characterizing the voids dispersion features of the SDVMs. Then on the basis of the characterization results, a reconstruction approach is developed based on the random medium theory and similarity comparison algorithm. The applicability and validity of the proposed voids dispersion characterization and SDVM reconstruction methods are verified through numerical and experimental case studies, respectively. And effects on the dispersion features of the SDVMs by such as autocorrelation function parameters and the sintering pressure are also investigated via the comparative discussions on the cumulative distribution function (cdf) curves of all dispersion parameters. Graphical abstract: Unlabelled Image Highlights: A parameter system consisting of A, l, α, and δ, is proposed for voids dispersion characterization. An approach is developed to reconstruct the stochastically distributed void morphologies with consistent voids dispersion. The proposed characterization and reconstruction methods are validated by numerical simulations and experimental results. Increase of sintering pressure changes the void dispersion morphology by altering parameters A, l and α, but not δ .